2014
DOI: 10.1073/pnas.1421410111
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates inactivate human EGFRs to exert antitumor actions

Abstract: Bisphosphonates are the most commonly prescribed medicines for osteoporosis and skeletal metastases. The drugs have also been shown to reduce cancer progression, but only in certain patient subgroups, suggesting that there is a molecular entity that mediates bisphosphonate action on tumor cells. Using connectivity mapping, we identified human epidermal growth factor receptors (human EGFR or HER) as a potential new molecular entity for bisphosphonate action. Protein thermal shift and cell-free kinase assays, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 36 publications
0
54
0
Order By: Relevance
“…Two-tailed Student's t test, *P ≤ 0.05, **P ≤ 0.01. (Table S1) osteoporosis and skeletal metastasis, has the potential for adjunctive use in EGFR-driven lung, breast, and other cancers (12,14). Two antihelminthic agents and a β-blocker similarly track on CMAP with a Gaucher disease gene signature (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two-tailed Student's t test, *P ≤ 0.05, **P ≤ 0.01. (Table S1) osteoporosis and skeletal metastasis, has the potential for adjunctive use in EGFR-driven lung, breast, and other cancers (12,14). Two antihelminthic agents and a β-blocker similarly track on CMAP with a Gaucher disease gene signature (13).…”
Section: Discussionmentioning
confidence: 99%
“…CMAP provides a unique strategy for unraveling new actions of drugs currently used for other medical conditions (13)(14)(15). The approach uses a gene signature to query the CMAP for gene expression profiles (https://portals.broadinstitute.org/cmap/).…”
Section: Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the physiologic mechanism of bisphosphonate action is complex, and they have been shown to block tumor growth independently of FPPS inhibition, namely through γ,δ T-cell receptor activation, [132,133] NF-κB inhibition, [134]. VEGF and hypoxia inducible factor-α suppression [135] as well as inactivation of epidermal growth factor receptors [136]. There is also a report showing that bisphosphonates target the three most epigenetic cell levels, namely DNA methylation, histone deacetylation and microRNAs [137].…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…We recently showed that aminobisphosphonates can inactivate human epidermal growth factor receptor (HER) family of receptor tyrosine kinases (RTKs) (4). We found that the drugs directly bind the HER1/2 kinase domain and, by inhibiting downstream signaling, reduce the cell viability in HER-driven lung, breast, and colon cancers (4). Knocking down the four HER isoforms abrogate bisphosphonate action, proving a selective action through this pathway (4).…”
mentioning
confidence: 99%